Self-Compassion, Mindful Eating, Eating Attitudes and Wellbeing Among Emerging Adults. Issue 1 (26th January 2022) - Shaw, Ruth; Cassidy, Tony
Abstract: Mindful eating behavior and self-compassion have been individually shown to contribute to healthy eating. Evidence suggests that they may interact and that interaction may increase our understanding of eating behavior. The aim of the current study was to explore the relationship between mindful eating behavior, self-compassion, healthy/unhealthy weight, eating disorder and wellbeing in a sample of university students. An online survey using questionnaire data collection in a sample of 349 students (105 males and 244 females). Variables measured included body mass index (BMI), mindful eating behavior, eating attitudes, self-compassion and mental wellbeing. Regression and path analysis show mindful eating behavior and self-compassion to individually and interaction predict eating attitudes and wellbeing. BMI was shown to have a curvilinear relationship with mindful eating behavior, self-compassion and wellbeing with both the underweight and obese reporting lower self-compassion, less Mindful eating behavior, lower wellbeing and more likely to exhibit disordered eating. These results indicate that self-compassion and mindful eating behavior might be usefully targeted in interventions to prevent both obesity and eating disorder.